Pathogenicity of the entomopathogenic fungi against Myllocerus fotedari Ahmad, 1974 (Coleoptera: Curculionidae) under laboratory conditions in India - Shaziya Gull; Ahmad Tariq; Abdul Lateef Khanday; Sureshan Pavittu Meethal; Gowhar Rashid (Journal of Forest Science, 2023)
The weevil, Myllocerus fotedari Ahmad, 1974 (Coleoptera: Curculionidae) is widely recognised as one of the major walnut pests. Fungal pathogens have shown great potential for the management of some pest species. In the present study, the efficacy of three entomopathogenic fungi, namely Beauveria bassiana (Balsamo) Vuillemin, Metarhizium anisopliae sensu lato (Metchnikoff) Sorokin and Lecanicillium lecanii (Zimmerman) Zare and Gams were evaluated against the weevil, M. fotedari, under laboratory conditions. Each fungal suspension contained 1.0 × 109 spores of fungi in 1 mL. The experiment comprised of five treatments along with control (distilled water) and three replicates. An insecticide - chloropyrifos 20% emulsifiable concentrate (EC), was also used as positive control in the experiment. The experimental results revealed that the weevil, M. fotedari, showed mortality due to both virulence of entomopathogens and insecticide. The mortality caused by fungi varied from two days after treatment to eight days after treatment. However, the highest mortality of 100% was recorded for B. bassiana, followed by 85.1% for M. anisopliae after eight days of treatment. The efficacy of L. lecani was the lowest, leading to only 51.8% mortality, and was found significantly less virulent compared to the other two used entomopathogens. The present study is an attempt to use entomopathogens to control M. fotedari over conventional chemical insecticides.